MICROBIAL DETOXIFICATION OF CYANIDE CONTENT IN CASSAVA WASTE:A SUSTAINABLE APPROACH - Fatimah Ibrahim Jumare; Madihah Md Salleh; Nurashikin Ihsan; Huszalina Hussin; Shafa'atu Giwa Ibrahim (SEAMEO BIOTROP, 2026)
ARTICLE HIGLIGHTS- Cassava waste with cyanide contamination presents significant environmental and health hazards. - Cyanide hydratase, nitrile hydratase, and rhodanese are microbial enzymes essential in the degradation of cyanogenic compounds.- The efficiency of cyanide degradation during fermentation is influenced by pH, temperature moisture content, and microbial strains.ABSTRACTCassava is a vital crop in tropical regions, known for its versatile applications in human and animal nutrition. Despite the potential of cassava byproducts, they contain cyanogenic glycosides such as linamarin and lotaustralin, which can hydrolyze to toxic cyanide, posing enormous environmental and health hazards. This review demonstrates microbial detoxification as an effective approach for mitigating cyanide contamination in cassava byproducts. Microorganisms such as Aspergillus, Bacillus, and Pseudomonas are known for their ability to detoxify cyanide via enzymatic mechanisms. These microorganisms facilitate β-cyanoalanine and rhodanese pathways that convert cyanide into non-toxic compounds. Comparative analysis of cassava waste fractions, leaves, peels, and bagasse showed that cyanide levels varied from 288.12 to 25.69 mg/kg, depending on processing, variety, and fermentation. This review highlighted the degradation of cyanide content from cassava waste via fermentation. The efficiency of submerged and solid-state fermentation processes can be affected by factors such as pH, temperature, microorganisms, and moisture content, achieving over 90% detoxification. However, solid-state fermentation offers a cost-effective, low-energy alternative, and submerged fermentation enhances microbial interaction for improved breakdown. Microbial methods offer a more environmentally sustainable alternative to chemical treatment, yet challenges related to scalability, optimization efficiency, and the necessity for resilient microbial strains remain. Nevertheless, the microbial degradation approach demonstrates significant potential for the biodegradation of cyanogenic compounds, offering a promising biological approach for detoxifying cyanide in cassava waste, reducing environmental pollution, and minimizing economic implications in waste valorization.